Lymphedema: Complications and Management - Agbenorku, Pius (Scientific Research, 2014)
Introduction: Lymphedema is a condition of the lymphatic system characterized by tissue swelling of body parts especially the limbs as a result of fluid retention. This debilitating condition may result in morbidity and immobility, incapacitating and causing economic burdens as well as affects the individual’s physiological and psychological well being. Aim: The aim of the review is to expound extensively on lymphedema and its associated complications and their management. Methods: Information was obtained by searching on-line literatures, published articles and news reports on lymphedema, causes, diagnoses, complications and personal clinical experience. Also patients’ data were obtained from Komfo Anokye Teaching Hospital Plastic Surgery Consulting Room and Surgical Operative Records in Kumasi, Ghana. Results: Extensive information was obtained from the various sources which formed the basis of this article highlighting especially the complications which include infections and lymphangiosarcoma resulting from long-standing untreated lymphedema. Conclusion: Since management of the condition is possible, patients are encouraged to seek early treatment when they experience any form of swelling. Long-standing lymphedema may result in serious complications including infections: cellulitis, lymphangitis and lymphangiosarcoma resulting from severe cases of untreated lymphedema.
Keywords: Lymphedema; Lymphatic System; Complications; Lymphangiosarcoma; Psychological; Physiological